Improved electrochemical performance for lithium-ion battery through titanium dissolving synthesis of diphase Li4Ti5O12 -TiO2 nanocomposite with prominent specific surface area. (20th January 2022) - Yan, Bei-Lei; Wang, Jun; Jun, Deng; Song, Qiu-Shi; Mu, Wen-Ning; Yang, Tao; Mao, Xue-Hua; Meng, Wei-Wei
Abstract: By means of developing a novel titanium dissolving slow hydrolysis method, a diphase Li4 Ti5 O12 -TiO2 nanocomposite sphere material with high grain boundary density was synthesized in situ, which showed improved rate capability and specific capacity when being applied to lithium-ion battery as an anode material. Due to a large amount of heat released during the dissolution of titanium powder, the sample with the primary structural morphology of nanosphere has the highest specific surface area of 124.6 m 2 g −1, and yielded good electrochemical performance in terms of high capacity (274 mAhg −1 at a current density of 0.5 C) as well as excellent cycling stability (135 mAhg −1 at a current density of 5 C up to 200 cycles). The outstanding electrochemical performance of the Li4 Ti5 O12 -TiO2 nanocomposite could be a result of the improved morphology, including the presence of high grain boundary density among the nanoparticles, Ti 3+ layering on each nanocrystal, and larger grain boundary interface areas. On this basis, the electronic transport properties were adjusted through interface design and nanometer-scale interface spacing, so as to provide more channels for the Li + ion insertion/extraction reactions. As a highly effective way to improve the electrochemical properties of Li4 Ti5 O12 -TiO2, a titanium dissolving slow hydrolysis mechanism promising to be the advanced batteries with denser volumetric energy, higher surface stability and longer cycle life than the common TBT hydrolysis in electrode materials. Therefore, it is ideal for being used as a high rate performance anode material for lithium-ion batteries.